2005
DOI: 10.1097/01.fjc.0000179625.89331.41
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Biodistribution of a pGT2-VEGF Plasmid DNA After Administration in Rats

Abstract: Intramyocardial administration of gene therapy vectors expressing angiogenic factors have been attempted as an alternative to conventional surgical methods for the management of myocardial ischemia. In this study, we have developed the pGT2-VEGF, a plasmid DNA vector expressing human VEGF165, for the management of ischemic cardiovascular disease and investigated in vivo pharmacokinetics and tissue distribution of pGT2-VEGF after intramyocardial and intravenous administration in rats. A high concentration of pG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The in vivo assessment of cardiac specificity was limited by the use of HTV injection for highly efficient hepatic transfection, which would be otherwise difficult to achieve with intramyocardial administration alone because of the limited half-life of plasmid DNA in blood (<5 min) 31. Biodistribution studies that are typically performed for viral vector-mediated gene delivery are not applicable here because of inadequate uptake and expression of plasmids in most non-cardiac tissues 32. Therefore, the in vivo results presented here do not comprise a complete assessment of tissue specificity, but do support the notion that the bidirectional TSTA strategy can effectively minimize extra-cardiac expression.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo assessment of cardiac specificity was limited by the use of HTV injection for highly efficient hepatic transfection, which would be otherwise difficult to achieve with intramyocardial administration alone because of the limited half-life of plasmid DNA in blood (<5 min) 31. Biodistribution studies that are typically performed for viral vector-mediated gene delivery are not applicable here because of inadequate uptake and expression of plasmids in most non-cardiac tissues 32. Therefore, the in vivo results presented here do not comprise a complete assessment of tissue specificity, but do support the notion that the bidirectional TSTA strategy can effectively minimize extra-cardiac expression.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by the fact that we were not able to detect significantly more myocardial VEGF expression after pcTnT-HIF-1a-VP2-TSTA-fluc delivery using enzymelinked immunosorbent assay (data not shown), even though we were able to detect significant FLuc expression or activation of the HIF-1a/HRE pathway (via the RLuc reporter) using the more sensitive reporter enzyme assays or BLI. Furthermore, because of the limited half-life of plasmid DNA in blood ( < 5 min) (Lew et al, 1995), biodistribution studies that are typically done for viral vector-mediated gene delivery were not useful here for assessing the transcriptional targeting capability of our bidirectional TSTA vector because of inefficient plasmid transfection in most noncardiac tissues (e.g., liver, lungs, spleens, kidneys) after intramyocardial vector delivery (e.g., < 1% of myocardial transfection in our preliminary studies; data not shown) (Son et al, 2005). Therefore, to both improve the therapeutic efficacy of our vector and allow for a better assessment of transcriptional targeting, we will need to incorporate our vector design into a high-capacity adenoviral vector for more efficient gene delivery.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, a viral vector will undoubtedly lead to more efficient myocardial transduction, thus making up for any loss of transgene expression due to the limited production of the GAL4-mER(LBD)-VP2 transactivator fusion protein secondary to cTnT’s known weak promoter activity. Second, the caveat of using a plasmid vector is that it does not lead to appreciable retention and expression in non-cardiac tissues (e.g., liver) following intramyocardial delivery despite fair amount of leakage from the myocardium [19]. The rapid clearance of plasmid in blood has been attributed to the working of plasma endonucleases, tissue surface enzymes, and non-parenchymal liver cells that act to scavenge and degrade plasmid DNA.…”
Section: Discussionmentioning
confidence: 99%